O uso da crioterapia em pacientes com osteoartrite de joelho - Ogura Dantas, Lucas (2020)
Knee osteoarthritis (OA) is a chronic progressive disease that brings a substantial socioeconomic burden to society and healthcare systems. Cryotherapy is a non-pharmacological intervention that is widely used by health care professionals for its effects on pain and inflammation. Compiling evidence about cryotherapy use and its efficacy may help to generate strategies for targeted knee OA rehabilitation. Thus, the objectives of this thesis were: 1) To investigate the effectiveness of cryotherapy on pain and physical function in knee OA; 2) To answer the question: Does short-term cryotherapy improve pain, function, and quality of life in people with knee OA? To achieve the first objective, we conducted a systematic review following the recommendations proposed by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses and the Cochrane Collaboration for systematic reviews. From the 338 studies identified, only five were included in the final analysis. Our review showed that cryotherapy modalities presented a low-quality level of evidence for pain control and functional outcomes among knee OA individuals. Besides, the mean PEDro score was 4.20/10, indicating the low methodological quality of the available studies. Therefore, there was an important literature gap to fill. To fill this gap and achieve the second objective, we conducted a randomized controlled trial (RCT) reported according to the Consolidated Standards of Reporting Trials Statement for Randomized Trials (CONSORT) of Nonpharmacologic Treatments and the Template for Intervention Description and Replication checklist (TIDieR) to verify the effects of short-term cryotherapy application on pain and physical function of individuals with knee OA. The trial was conducted over a period of 6 consecutive days and 60 patients were randomized into two groups: an experimental group that received cryotherapy (ice packs), and a control group that received a sham intervention (sand packs). Our study showed that cryotherapy was not superior to a sham intervention in terms of relieving pain or improving function and quality of life in people with knee OA. Other research included: with the results of our first RCT, we developed a protocol for a second RCT to verify the complementary effects of cryotherapy (long-term use) on pain and function when associated with a tailored therapeutic exercise protocol for patients with knee OA. Also, we included on this thesis a masterclass about knee OA to guide therapists on their clinical practice and decision making. All manuscripts included on this thesis are published.